2021
DOI: 10.1038/s41388-021-01718-4
|View full text |Cite|
|
Sign up to set email alerts
|

YAP1 overexpression contributes to the development of enzalutamide resistance by induction of cancer stemness and lipid metabolism in prostate cancer

Abstract: Metastatic castration-resistant prostate cancer (mCRPC) is a malignant and lethal disease caused by relapse after androgen-deprivation (ADT) therapy. Since enzalutamide is innovated and approved by US FDA as a new treatment option for mCRPC patients, drug resistance for enzalutamide is a critical issue during clinical usage. Although several underlying mechanisms causing enzalutamide resistance were previously identified, most of them revealed that drug resistant cells are still highly addicted to androgen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…These results suggest that TSP1 could be employed as a biomarker to predict resistance to ARPIs and to diagnose NED in CRPC patients [109]. Another study described the expression of YAP1 and COUP-TFII in EVs from LNCaP-Enzalutamide resistant cells as well as sera from patients resistant to enzalutamide [110].…”
Section: Evs As Source Of Biomarkers To Predict Therapeutic Resistances In Pca 41 Evs Content To Find New Predictive Biomarkersmentioning
confidence: 84%
See 1 more Smart Citation
“…These results suggest that TSP1 could be employed as a biomarker to predict resistance to ARPIs and to diagnose NED in CRPC patients [109]. Another study described the expression of YAP1 and COUP-TFII in EVs from LNCaP-Enzalutamide resistant cells as well as sera from patients resistant to enzalutamide [110].…”
Section: Evs As Source Of Biomarkers To Predict Therapeutic Resistances In Pca 41 Evs Content To Find New Predictive Biomarkersmentioning
confidence: 84%
“…A miR-array study has also identified 29 deregulated miRNAs, 19 upregulated and 10 downregulated, in EVs samples derived from two paclitaxel resistant PCa cells (PC3 and DU145) compared with their parental cells, but miR expression in patients has not been investigated [86]. miR-21 expression was increased in EVs from enzalutamide resistant LNCaP cells as well as in sera of enzalutamide resistant patients [110].…”
Section: Evs As Source Of Biomarkers To Predict Therapeutic Resistances In Pca 41 Evs Content To Find New Predictive Biomarkersmentioning
confidence: 99%
“…Moreover, DECR1 deletion decreased lipid metabolism of CRPC in vivo (6). Another study discovered that knockdown of YAP1 led to restored lipid content and reduced free fatty acid level in enzalutamide-resistant cells (20).…”
Section: Crpc Metabolismmentioning
confidence: 96%
“…The important transcription regulators, SOX2, OCT4, and NANOG, contribute to the maintenance of the pluripotent state of CSCs. Some studies indicated that inhibition of androgen receptor (AR) function increases the stemness of PCSCs [44,45]. MDM2 mediates AR degradation to maintain the pluripotency of PCSCs.…”
Section: Prostate Cancer Stem Cellsmentioning
confidence: 99%